2016
DOI: 10.18632/oncotarget.8257
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA MALAT1 promotes malignant development of esophageal squamous cell carcinoma by targeting β-cateninviaEzh2

Abstract: Evidences have shown that lncRNAs involve in the initiation and progression of various cancers including esophageal squamous cell carcinoma (ESCC). The aberrant expression of lncRNA MALAT1 was investigated in 106 paired ESCC tissues and adjacent non-cancerous tissues by qRT-PCR. Down-regulated MALAT1 and Ezh2 over-expression plasmid were constructed respectively to analyze the expression of β-catenin, Lin28 and Ezh2 genes. We found that the MALAT1 expression level was higher in human ESCC tissues (P=0.0011), w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(75 citation statements)
references
References 39 publications
1
74
0
Order By: Relevance
“…Wang et al. recently found that the expression of lncRNA MALAT1 were higher in ESCC tissues and cell lines. Downregulation of MALAT1 decreased the expression of β ‐catenin, Lin28, and EZH2 genes, while overexpressed EZH2 could reverse such suppressive effect, indicating the promotion mechanism of MALAT1 in ESCC.…”
Section: Discussionmentioning
confidence: 98%
“…Wang et al. recently found that the expression of lncRNA MALAT1 were higher in ESCC tissues and cell lines. Downregulation of MALAT1 decreased the expression of β ‐catenin, Lin28, and EZH2 genes, while overexpressed EZH2 could reverse such suppressive effect, indicating the promotion mechanism of MALAT1 in ESCC.…”
Section: Discussionmentioning
confidence: 98%
“…MALAT1 has been reported to be an oncogenic lncRNA which can promote cancer development by acting as miRNA sponges, regulating autophagy, or accelerating EMT signaling (Chou et al, ; Li et al, ). MALAT1 can promote tumor development in various cancers, such as gallbladder cancer (Wang, Zhu et al, ), gastric cancer (Xia et al, ) and esophageal squamous cell carcinoma (Wang, Yu et al, ). For instance, MALAT1 can promote gallbladder cancer development by sponging miR‐206 (Wang, Zhang, Wu, Weng et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…As one of the first identified cancer‐associated lncRNAs, MALAT1 was reported to be overexpressed in gastric cancer (Chen, Liu, Wang et al, 2017), breast cancer (Arun et al, ), prostate cancer (Ren et al, ), cervical cancer (Sun, Qin et al, ), acute myeloid leukemia (Chen, Nagel et al, 2018), medullary thyroid cancer (Chu, Hardin, Schneider, Chen, & Lloyd, ), choriocarcinoma (Shi, Wang, & Yin, ), gallbladder cancer (Sun et al, ), pancreatic cancer (Xie et al, 2017), multiple myeloma (Liu, Wang et al, ), ovarian cancer (Wu et al, 2017), T and natural killer cell lymphoma (Kim, Kim, Yang, Kim, & Yoon, ), acute monocytic leukemia (Huang, Liu et al, ), endometrial stromal sarcoma (Yamada et al, ), myeloma (Cho et al, ), clear cell renal cell carcinoma (Zhang, Yang, Chen, Che, & Zheng, ), esophageal squamous cell carcinoma (Hu et al, ), glioma (Ma, Wang, Li et al, ), osteosarcoma (Cai et al, ), neuroblastoma (Tee et al, ), tongue squamous cell carcinomas (Fang et al, ), hilar cholangiocarcinoma (Tan, Huang, & Li, ), mantle cell lymphoma (Wang, Zhu et al, ), and other tumor tissues. It has been reported that MALAT1 is involved in the regulation of tumor proliferation, apoptosis, invasion, metastasis, and angiogenesis.…”
Section: Physiopathological Role Of Malat1mentioning
confidence: 99%